Medical Malpractice Claims and Mitigation Strategies Following Spine Surgery. Issue 5 (June 2021) - Jackson, Keith L.; Rumley, Jacob; Griffith, Matthew; Linkous, Timothy R.; Agochukwu, Uzondu; DeVine, John
Study Design: Narrative review. Objective: The aim of this narrative review is to examine trends in malpractice litigation arising from spine surgery. We also hope to detail mitigation strategies that surgeons can employ to decrease their risk of a claim. Methods: A review of the relevant literature examining the prevalence, risks, and outcomes of malpractice litigation following spine surgery was conducted using the MEDLINE and Embase databases. Results: Combined queries identified 1140 potentially relevant articles. After eliminating duplicate articles and screening by title and abstract, 38 articles underwent full-text review. Of these, 22 were deemed relevant to the research questions posed. Evaluation of references identified 1 additional relevant article. Spine surgery represents one of the most litigious specialties in the United States health care system. The available literature points to a consistent pattern of common allegations leading to litigation following spine surgery. While a majority of filed lawsuits end in the surgeon's favor, these cases carry high monetary and time expenditures regardless of outcome. Furthermore, the threat of a malpractice lawsuit motivates many surgeons to practice defensive medicine by utilizing unnecessary or unindicated tests and studies. Conclusion: Through the examination of trends in malpractice claims and case outcomes, surgeons may be able to adapt practices to minimize their risk of litigation. These changes can include, but are not limited to, identification of those procedures that are most litigious and a more thorough discussion of the informed consent process to include operative and nonoperative treatments prior to all procedures. More important, however, spine surgeons can potentially serve as advocates for change.